Administration of melatonin prior to modified synchronization protocol improves the productive and reproductive efficiency of Chinese crossbred buffaloes in low breeding season - Abulaiti, Adili; Nawaz, Mudussar; Naseer, Zahid; Ahmed, Zulfiqar; Liu, Wenju; Abdelrahman, Mohamed; Shaukat, Aftab; Sabek, Ahmed; Pang, Xunsheng; Wang, Shujuan (Frontiers in Veterinary Science, 2023)
Abstract: Introduction: Melatonin is a neurohormone involving various biological processes, including restoration of cyclicity in animals with seasonal breeding patterns. The use of melatonin in different forms has gained broader acceptance in different species, particularly in summer anestrous buffaloes. Objectives: The objective of the current study was to evaluate the melatonin effect on the reproductive and productive performance of crossbred buffaloes during the low breeding season. Methods: Sixty-five cyclic and reproductively sound crossbred buffaloes were randomly allocated to three groups: the G1 (n=20) served as the control group and received no single melatonin, G2 received melatonin (n=22; 18 mg/50kg, body weight) once prior to synchronization and G3 group was administered multiple melatonin injections (n=23; 6mg/50kg body weight) for three consecutive days before the start of the synchronization protocol. The reproductive performance, milk yield traits, and serum immunoglobulin M (IgM) and melatonin levels were evaluated in treated and untreated crossbred buffaloes. Results: The results revealed that a single dose of melatonin administration has (P<0.05) improved estrus response, ovulation occurrence and follicular growth in crossbred buffaloes compared to control groups. Higher pregnancy rates were observed in both melatonin-treated buffalo groups compared to the control. Following the administration of melatonin, serum IgM level increased in G2 and G3; however, an increment in melatonin level (P<0.05) was detected in the G2 group only as compared to the control group subsequent day of melatonin administration. The milk compositions were not affected by melatonin administration except for milk urea nitrogen and somatic cell count (SCC). The melatonin administration (P<0.05) decreased the somatic cell count in buffalo milk compared to untreated. Conclusion: In conclusion, single or multiple doses of melatonin before initiating the synchronization protocol improved the ovulation, ovulatory follicle diameter and pregnancy rates in crossbred buffaloes during the low breeding season. Moreover, the administration of melatonin enhanced the IgM values along milk traits in terms of milk protein, MUN and somatic cell count in treated buffaloes.